Financial integration, globalization, and real activity - Gianni De Nicolò; Luciana Juvenal (Center for Economic Studies and ifo Institute (CESifo), 2012)
Using data for a large number of advanced and emerging market economies during 1982-2009, this paper examines the distinct impact of financial integration and globalization on several dimensions of real activity. We find that: (a) financial integration has progressed significantly worldwide, particularly in emerging markets, as well as within regions; (b) advances in financial integration predict better growth prospects; (c) both advances in financial integration and globalization are associated with higher growth, lower growth volatility, and lower probabilities of severe declines in real activity. Advances in financial integration and globalization indeed foster countries' growth, and there appears to be no trade-off between these advances and macroeconomic stability.
Keywords: F36; G15; 330; financial integration; globalization; real activity; Internationaler Finanzmarkt; Marktintegration; Globalisierung; Wirtschaftswachstum; Konjunktur; Schätzung; Industriestaaten; Schwellenländer